Subcutaneous paratibial fasciotomy in the treatment of chronic venous ulcer - Leković Ivan; Mišović Sidor; Bjelanović Zoran; Drašković Miroljub; Tomić Aleksandar (Vojnosanitetski Pregled)
Background/Aim. Chronic venous ulcer (CVU), a disease of high incidence, is one of the most serious chronic venous insufficiency complications. It has been estimated that there are 1%-2% of adults with CVU deriving a high social significance. The aim of this study was to, using the clinical experience, determine the influence of subcutaneous paratibial fasciotomy (SPF) on the course and the treatment outcome of CVU. Methods. From February 2006 to September 2009 SPF was applied in a group of 43 patients treated for CVU along with other standard methods of treatment, and its influence on the course of ulcus cruris was followed up regarding the control group of another 43 patients treated with standard methods with no paratibial fasciotomy. Results. In the group of patients treated with SPF there was a significantly better clinical course of ulcus cruris closing as compared with the group of patients in which this method was not applied. In the group with paratibial fasaciotomy there was no Thiersch skin transplant rejection recorded nor ulcus recurrence within a 6-month after-surgery period, while in the control group there was Thiersch skeen transplant rejection in 11 patients, and ulcus recurrence in 9 patients within the same period. Conclusion. SPF is a useful method with a favorable influence on better clinical course of ulcus cruris closing, reducing recurrence rate and improving local microcirculation in the affected region. Operation act itself is safe, requires no specific equipment nor special training of the team of surgeons, thus being applicable to the majority of patients with ulcus cruris indicated for surgery.